Income Inequality and Economic Freedom Revisited: Are Freedom and Equality Conflicting Values? Evidence from the Twenty-First Century - Machado, Carlos Daniel Pereira (2022)
Dissertação de Mestrado em Economia apresentada à Faculdade de Economia